Research on the breaking mechanism of bolts and cables in the gateway driven along a small coal pillar in the Datong mining area and the corresponding control technology - Peng, Cheng (Frontiers in Earth Science, 2023)
The gateway of thick coal seam working face in Datong mining area was excavated along a small coal pillar, resulting in serious bolt (cable) breaking failure, strong surrounding rock deformation, serious ground pressure appearance and difficult surrounding rock control. So, the bolts (cables) breaking characteristics and corresponding causes of 5106 return air gateway with a small coal pillar in Dongzhouyao coal mine (a mine in Datong mining area) were analyzed through on-site investigation, surrounding rock geotechnical parameters test, theoretical analysis, laboratory experiment, on-site engineering test and other research means. The study carried out laboratory testing and analysis on the stress distribution characteristics and laws of the bolts, put forward the bolts (cables) breaking mechanism and prevention countermeasures, and completed the field industrial test of the surrounding rock pressure relief and support joint control technology in the gateway. The on-site tracking and data showed that the breaking conditions of the bolts (cables) were significantly reduced by improving the initial force of the bolts (cables), optimizing the supporting materials and components, canceling the pressure ring, and implementing the hydraulic fracturing top cutting and pressure relief + high prestressed full cable support technology. The displacement of the top and bottom plates was reduced by 51%, the displacement of the two sides was reduced by 46%, and the influence distance of the working face advance stress was reduced from 85 m to 30 m. The successful implementation of the study results in the small pillar gateway of Dongzhouyao coal mine provided a reference for the promotion and application of similar gateway conditions in Datong mining area.